(untitled) (Fiep Bulletin - online, 2011)
The study is characterized as a bibliographical research that presents as field of discussion the Brazilian theoretical production on the dance as content of education in the schools. In this direction, it objective to identify and to analyze the investigative conceptions and trends that have guided articles, theses, dissertations that discuss the inclusion of dance in physical education classes. It concluded that understanding the dance beyond the technical, through improvisation and free expression of the student is giving it new meaning, transforming its movements, changing its image. This is possible because the dance is not crystallized, had and has a constant transformation in the productions human beings in agreement the reality where if they insert.